Coerced work during parole: prevalence, mechanisms, and characteristics - Augustine, Dallas (Criminology, 2023)
Coerced work on parole occurs when people are required to work under the threat of criminal legal repercussions. In the face of barriers to "good" work for people after prison, coercion helps to funnel parolees into positions at the bottom of the labor market. Parolee workers in these positions experience issues common to precarious, low-wage work (low pay, hazardous working conditions, and labor law violations), as well as heightened vulnerability to predatory employers and exposure to parole-prohibited activities. Because of the threat-backed requirements to work, however, parolees must choose to either accept this "bad" work or face potential sanctions. Using mixed-methods, including a novel form of respondent-driven sampling I call "Hybrid-RDS," this article documents the prevalence of coerced work for people on parole in Los Angeles County, identifies the mechanisms through which coercive work operates, and illustrates the problematic employment conditions of coerced work after prison.